Veil Type Selection Based on Perceptions of its Main Function: Its Impact on Fashion Spending - Fitri, Wahyu Annisa; Mustion, Seppi; Sausan, Putri Diani (Journal of Islamic Economic Scholar, 2022)
As time goes by, veil (the hijab) which is originally an obligation enacted by the religious teaching, nowadays developed into a fashion trend. Veil is not just a simple fashion component with the main purpose of covering the female head and another part of body which should not be seen by the others (aurat). Certain accessories often become addition to veil (fashionable) due to the aesthetic reason making it demands a greater spending rather than not wearing any veil at all. It is a veiling phenomenon that we might call as the “Above Mecca, below Mall” style. On the other hand, internalized value as a component of VBN (Value-Belief-Norm) theory might be more dominant in affecting her subjective norm and therefore translated into her perception that veiling is an obligation of religious teaching which she must obey rather than the surrounding external environment such as trends among her peer groups or workplace rules. Our raw data was collected from 150 female students divided into 3 groups; veil weares type-1 (sharia veil), type-2 (fashionable veil) and non (non-veil) wearers, from 5 universities in Padang City, West Sumatra Province. The analysis was done in two sequential steps. Firstly, we revealed which one among the two concepts is the most prioritized and converted it into a score using an important variable named perception using AHP (Analytical Hierarchical Process) instrument. As the second step, multinomial logit model was used as the first-stage of 2-SLS regression where the perception score is one of several dependent variables, then an outcome prediction (what) was used at the second instrumented stage on veil type wearers. The study found that veil type-1 users have smaller fashion spending allocation rather than the two other sample groups. This indicates that marketers should design their strategies keeping in mind that female college students consumers at Padang city are influenced by significant others when making their purchasing decisions